Skipped Zonal based Binary DCT (SZBinDCT) for Image communication over Resource Constrained Visual Sensor Network - G. Suseela; Asnath Victy Phamila Y (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The contemporary advancements in CMOS technology and Multimedia systems enabled image communication over resource constrained Visual Sensor Network (VSN). However, the size of image data is huge. It is wise to send the compressed image over the bandwidth limited network. Compression algorithms also should be of energy efficient with low complexity and should offer acceptable image quality. In this work an image coder offering low bit rate less than 0.5bpp is aimed. In this paper, a low memory and energy efficient skipped zonal based Binary DCT is proposed that codes the transformed samples using Golomb Rice code. Simulation results offered low bitrate 0.39 bpp with PSNR of 27.34 dB for the standard gray scale test image of Lena size 512 x512 pixels.